Phylogenomic Analysis of the Phylum Nematoda: Conflicts and Congruences With Morphology, 18S rRNA, and Mitogenomes - Ahmed, Mohammed; Roberts, Nickellaus G.; Adediran, Funmilola; Smythe, Ashleigh B.; Kocot, Kevin M.; Holovachov, Oleksandr (Frontiers in Ecology and Evolution, 2022)
Phylogenetic relationships within many lineages of the phylum Nematoda remain unresolved, despite numerous morphology-based and molecular analyses. We performed several phylogenomic analyses using 286 published genomes and transcriptomes and 19 new transcriptomes by focusing on Trichinellida, Spirurina, Rhabditina and Tylenchina separately, and by analyzing a selection of species from the whole phylum Nematoda. The phylogeny of Trichinellida supported the division of Trichinella into encapsulated and non-encapsulated species and placed them as sister to Trichuris. The Spirurina subtree supported the clades formed by species from Ascaridomorpha and Spiruromorpha respectively, but did not support Dracunculoidea. The analysis of Tylenchina supported a clade that included all sampled species from Tylenchomorpha and placed it as sister to clades that included sampled species from Cephalobomorpha and Panagrolaimomorpha, supporting the hypothesis that postulates the single origin of the stomatostylet. The Rhabditina subtree placed a clade composed of all sampled species from Diplogastridae as sister to a lineage consisting of paraphyletic Rhabditidae, a single representative of Heterorhabditidae and a clade composed of sampled species belonging to Strongylida. It also strongly supported all suborders within Strongylida. In the phylum-wide analysis, a clade composed of all sampled species belonging to Enoplia were consistently placed as sister to Dorylaimia + Chromadoria. The topology of the Nematoda backbone was consistent with previous studies, including polyphyletic placement of sampled representatives of Monhysterida and Araeolaimida